Synthesis and anticonvulsive activity of fluorine-substituted benzhydrylamides; Pharmaceutical Chemistry Journal; Vol. 31, iss. 7 - Krasnov V. A.; Gorshkova V. К.; Bakibaev A. A. Abdigali Abdimanapovich; Saratikov A. S. (1997, 1997)
Title screen